2018
DOI: 10.1111/jfbc.12631
|View full text |Cite
|
Sign up to set email alerts
|

The effects of supplementation with vitamin D on inflammatory biomarkers, omentin, and vaspin in women with type 2 diabetes: A randomized double‐blind placebo‐controlled clinical trial

Abstract: Type 2 diabetes (T2DM) is a global problem that increases the risk of inflammation and hormonal dysfunction. The purpose of this study was to determine the effect of vitamin D on inflammatory biomarkers, omentin, and vaspin in diabetic women with anxiety. In this study, 51 women with T2DM were allocated to receive one oral pearl of 50,000 IU vitamin D3 (26) or a placebo (25) fortnightly for 16 weeks. Anthropometric indices, dietary intake, high sensitivity C‐reactive protein (hs‐CRP), Interleukin 10 (IL‐10), v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…14 Fazelian et al have compared omentin-1 levels and vitamin D, before-and after-treatment, in female patients of type 2 diabetes mellitus. He observed significantly raised omentin-1 levels with high levels of vitamin D. 15 Very few studies have been conducted to assess the relationship between vitamin D and omentin-1, however; literature has given the association between 16 Similarly, Gangloff et al; observed the positive correlation between vitamin D and leptin in young males with central obesity. 17 Mohammad SM et al worked on another adipokine adiponectin in diabetic patients and found high vitamin D levels with high adiponectin values.…”
Section: Discussionmentioning
confidence: 99%
“…14 Fazelian et al have compared omentin-1 levels and vitamin D, before-and after-treatment, in female patients of type 2 diabetes mellitus. He observed significantly raised omentin-1 levels with high levels of vitamin D. 15 Very few studies have been conducted to assess the relationship between vitamin D and omentin-1, however; literature has given the association between 16 Similarly, Gangloff et al; observed the positive correlation between vitamin D and leptin in young males with central obesity. 17 Mohammad SM et al worked on another adipokine adiponectin in diabetic patients and found high vitamin D levels with high adiponectin values.…”
Section: Discussionmentioning
confidence: 99%
“…Jafari et al [38] reported that the intake of vitamin D-fortified low-fat yogurt decreased hs-CRP, and improved inflammation and the omentin plasma concentration, independent of a change in body weight or BMI. Similarly, vitamin D supplementation for 16 weeks decreased hs-CRP while increasing IL-10 and omentin plasma concentration [44]. Omentin acts as an anti-inflammatory factor in patients with diabetic obesity [21], as well as one of the mediators of the antioxidant effect of vitamin D [45].…”
Section: Discussionmentioning
confidence: 99%
“…For example, statins were shown to decrease the transcription of the KRT6A gene, and subsequent case reports have reported benefits in patients with pachyonychia congenita caused by KRT6A mutations. Vitamin D has been shown to correlate with SERPINA12 levels, but one study found that vitamin D supplementation (50,000 IU/week) did not improve SERPINA12 levels (Fazelian et al, 2018).…”
Section: Future Therapeutic Implicationsmentioning
confidence: 99%